Frequency and Problems Associated With Retinopathy of Prematurity (ROP) in A Tertiary Care Hospital - Rahman, Sabira; Shanta, Nayeema Ferdous; Morshed, Mashura; Mili, Saifa Lubna; Khan, Masuma; Sarkar, Arpita (Journal of Dhaka Medical College, 2024)
Background: Retinopathy of prematurity (ROP) is a retinal disease that principally affects preterm infants. It is recognized as the leading cause of preventable blindness and visual impairment in the pediatric population. An increase in survival of very young preterm infants due to the advances in neonatology has subjected them to the risk of developing ROP. Aims & Objectives: To find out the frequency and problems associated with Retinopathy of Prematurity (ROP) in premature babies. Materials and Methods: This observational study was conducted at Dhaka Medical College and Hospital from July 2016-December 2016. A total of 73 preterm neonates with gestational age less than 35 weeks and weighing less than 2000 grams at birth, being born or admitted at Dhaka Medical College and Hospital were included in the study. After purposive sampling who had fulfilled the inclusion criteria and screened for ROP at 4 weeks after birth. The data analysis was done to find out the prevalence and problems associated with ROP of premature babies. Result: A total of 73 neonates were screened. The prevalence of ROP was found to be 54% (n=40); of which 35% were in stage 1 and 35% were in stage 2 and the majority were in zone 3 (50%). The prevalence of ROP between 28-30 weeks of gestation was 75% (n=12) and between 31-34 weeks was 49.12% (n=28). 50% (20) neonates with birth weights less than 1500 grams were found to develop ROP. The prevalence of post-natal problems that predispose to ROP was oxygen therapy, apnea, blood transfusion, and sepsis, and the P-value was significant. Out of ROP-positive cases, 16(40%) need laser photocoagulation. Conclusion: The prevalence of Retinopathy of Prematurity (ROP)in premature babies is high below 30 weeks of gestational age and birth weight less than 1500 gm. Problems significantly associated with ROP were oxygen therapy, apnea, blood transfusion, and sepsis. J Dhaka Med Coll. 2022; 31(2) : 237-242